Abstinence and reduced frequency of use are associated with improvements in quality of life among treatment‐seekers with cannabis use disorder. (19th February 2018) - Brezing, Christina A.; Choi, C. Jean; Pavlicova, Martina; Brooks, Daniel; Mahony, Amy L.; Mariani, John J.; Levin, Frances R.
Abstract : Background And Objective: Many patients with cannabis use disorder (CUD) do not achieve or do not have abstinence as a goal of treatment, rather they reduce their use. Assessing outcome measures as they relate to functioning and reductions in cannabis use is an important area of study. Quality of life (QoL) shows promise as one such measure. Past studies have demonstrated gender differences in QoL and CUD. We aim to assess (1) the relationship between cannabis use and QoL and (2) gender effects in an outpatient medication treatment study for CUD. Methods: Data from an 11‐weeks, double‐blind, placebo‐controlled trial of lofexidine and dronabinol for CUD ( n = 62) was analyzed. Pearson's correlations between baseline QoL as measured with the Quality of Life, Enjoyment, and Satisfaction Questionnaire‐Short Form (QLES‐Q‐SF) and cannabis use assessed with modified timeline follow‐back (TLFB) were examined. Multiple linear regression models of cannabis use on end of study QLES‐Q‐SF were analyzed, while adjusting for baseline QLES‐Q‐SF, study arm, and gender. Moderation effects with gender were also tested. Results: No significant association between baseline cannabis use and QoL was found. End of study abstinence ( F 1, 47 = 8.34, p = .006) and reduced proportion of using days ( F 1, 47 = 9.48, p = .004) were each significantly associated with end of study QoL. Reduction in grams ( F 1, 27 = 0.25, p = .62) was not associated with QoL at end of study. Gender was not a significant moderator. Discussion and Conclusions: Abstinence and lower frequency of use are associated with higher QoL, regardless of gender. Scientific Significance: This is the first time QoL has been demonstrated to change over the course of CUD medication treatment. QoL is an important outcome in CUD treatment. Trial Registration: NCT01020019. (Am J Addict 2018;27:101–107).